Determinants of Male Participation in Using Contraception Based on Transcultural Nursing Theory - Bestfy Anitasari; Lestari Lorna Lolo; Grace Tedy Tulak (Universitas Aisyah Pringsewu, 2023)
Culture becomes an inseparable part of the formation of a person's health behavior. One of them is participation in family planning programs. Currently, the participation of men in family planning programs is still lacking. This study aims to determine the determinants of men participating in family planning programs based on the theory of transcultural nursing. The research method is descriptive quantitative with a cross-sectional design. The number of respondents as many as 178 people obtained by purposive sampling. This study's instrument was a questionnaire adapted from the Transcultural Nursing theory assessment format and had been tested for validity and reliability before. The results of the research on technological factors have a strong relationship (p = 0.000), religious and philosophical factors have a weak relationship (p = 0.002), social factors and family attachments have a strong relationship (p = 0.001), cultural values, beliefs and lifestyle factors have a weak relationship (p = 0.001), political and legal factors have a strong relationship (p = 0.000), economic factors have a strong relationship. weak (p = 0.000), the education factor has a strong relationship (p = 0.000). The most influential factors on men's participation in family planning programs are social factors and family attachments followed by educational factors. The government and family planning field officers are expected to be more active in intensifying the promotion of family planning for both women and men directly and through print, electronic and social media. Abstrak: Kebudayaan menjadi bagian yang tidak terpisahkan dari pembentukan perilaku kesehatan seseorang. Salah satunya yaitu keikutsertaan dalam program keluarga berencana. Saat ini, partisipasi pria dalam program keluaga berencana masih kurang. Penelitian ini bertujuan untuk mengetahui faktor determinan pria berpartisipasi dalam program keluarga berencana berdasarkan teori transcultural nursing. Metode penelitian adalah kuantitatif deskriptif dengan desain cross sectional. Jumlah responden sebanyak 178 orang yang didapatkan dengan purposive sampling. Instrumen dalam penelitian ini adalah kuesioner yang diadaptasi dari format pengkajian teori Transkultural Nursing dan telah diuji validitas dan realibilitas sebelumnya. Hasil penelitian faktor teknologi memiliki hubungan yang kuat (p=0,000), faktor agama dan filosofi memiliki hubungan yang lemah (p= 0,002), faktor sosial dan keterikatan keluarga memiliki hubungan yang kuat (p= 0,001), faktor nilai budaya, keyakinan dan gaya hidup memiliki hubungan yang lemah (p= 0,001), faktor politik dan legal memiliki hubungan yang kuat (p= 0,000), faktor ekonomi memiliki hubungan yang lemah (p= 0,000), faktor pendidikan memiliki hubungan yang kuat (p= 0,000). Faktor yang paling berpengaruh terhadap partisipasi pria dalam program keluarga berencana adalah faktor sosial dan keterikatan keluarga diikuti faktor pendidikan. Pemerintah dan petugas lapangan keluarga berencana diharapkan semakin aktif menggencarkan promosi keluarga berencana baik bagi wanita maupun pria secara langsung maupun melalui media cetak, elekronik dan sosial.